Non-invasive assessment of acute heart failure by Stevenson classification: Does echocardiographic examination recognize different phenotypes? - Palazzuoli, Alberto; Ruocco, Gaetano; Valente, Serafina; Stefanini, Andrea; Carluccio, Erberto; Ambrosio, Giuseppe (Frontiers in Cardiovascular Medicine, 2022)
Background- Acute heart failure (AHF) presentation is universally classified in relation to the presence or absence of congestion and perfusion condition according to the Stevenson diagram. Up to now, no data are reported in literature comparing clinical and echocardiographic evaluation. Aims- we sought to evaluate a relationship existing between clinical assessment and echocardiographic evaluation in AHF patients and to verify if a simplified echocardiographic strategy could modify initial Stevenson presentation. Methods- this is a retrospective blinded multi centre analysis assessing both clinical and echocardiographic analyses during the first 6 hours since hospital admission for a AHF. Clinical assessment according to the Stevenson classification was performed: patients were categorized into 4 groups. Group A (warm and dry), Group B (cold and dry) Group C (warm and wet) Group D (cold and wet). Echocardiographic evaluation was executed within 12 hours from the first clinical evaluation. The following parameters were measured: Left Ventricular (LV) volumes, LV ejection Fraction (LVEF); pattern doppler by E/e1 ratio, systolic pulmonary artery pressure (PASP), Tricuspid annular plane systolic excursion (TAPSE) and inferior cave vein diameter (ICV). Results- we studied 208 patients, 10 in group A, 10 in group B, 169 in group C and 29 in group D. Median age of our sample was 81 [69-86] years and the patients enrolled were mainly men (66.8%). PASP and TAPSE values were higher in patients of group C compared to group A, B and C (45 [35-55] mmHg vs 32 [29-46] mmHg vs 40 [29-46] mmHg vs 45 [36-54] mmHg, p=0.045; 18 [14-20] mm vs 17 [16-21] mm vs 14 [12-17] mm vs 16 [12-17] mm, p=0.016). Patients in groups A and C demonstrated significant higher values of LVEF with respect to patients in groups B and D (43 [34-55]% vs 40 [29-51]% vs 30 [25-41]% vs 30 [22-44]%, p=0.018). Finally, echocardiographic congestion score including PASP≥40 mmhg, ICV ≥21 mm and E/e’>14, did not differ among groups. Conclusions- the early Stevenson classification remains a universally recognized approach for the detection of congestion and perfusion status. The combined clinical and echocardiographic assessment may be useful to better classify patients profile .